STRATEGI GURU DALAM PEMANFANFAATAN MEDIA DIGITAL KOMPUTER UNTUK MENINGKATKAN LITERASI MEMBACA SISWA SD - Putri Amelia, Helen; Moh Toharudin; Muamar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension skills in elementary school students still need attention because some students experience difficulties in understanding reading texts even though they are already able to read fluently. In the learning process, the use of less varied learning media often makes students feel bored and less focused during reading activities. The use of computer-based digital media can be an alternative for teachers to create more interesting reading instruction and encourage students to be more active during learning activities. This study aims to determine teachers’ strategies in utilizing computer digital media to improve elementary school students’ reading literacy. The study used a qualitative approach with a literature review design. Data were obtained from scientific journals, books, research articles, and academic documents related to teacher strategies, computer digital media, and reading literacy. Data collection techniques were carried out through documentation studies, while data analysis used descriptive qualitative analysis. The results of the study show that teachers’ strategies have an important role in the use of computer digital media in reading instruction. Teachers play a role in preparing learning activities, guiding students during reading activities, and evaluating students’ comprehension. In addition, the use of computer digital media helps create more interesting learning activities, makes students more focused, and helps students understand reading texts better.